(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
Germline gene editing represents one of the most controversial and fascinating frontiers of current scientific research. Until recently, the very few experiments carried out in this field hadn’t pursued a reproductive goal, as the scientific community agreed on the fact that the technique is still in its infancy, and thus any clinical application would have been unethical and premature. However, the announcement made last November by Chinese researcher Jiankui He at the Second International Summit on Human Genome Editing in Hong Kong – stating that he would have helped making the world’s first genome-edited babies – seems to have turned germline gene editing from a speculative reality into a practical and concrete one. The aim of the present work is to identify and analyze the main ethical, scientific and legal issues raised by this experiment, which triggered great criticism both in the scientific community and in the public. This analysis will be preceded by a brief description of the case, as well as by the examination of the main supranational and international regulations and an overview of the experiments conducted so far in the field under discussion. This will lead to a few conclusive critical remarks on some debated aspects of Jiankui He’s case and on some possible, future perspectives related to the use of germline gene editing techniques for therapeutic purposes.